Agenda navigation in consultations covering multiple topics. A qualitative case study from general practice - Ann Dorrit Guassora; May-Lill Johansen; Kirsti Malterud (Taylor & Francis Group, 2021)
Objective To explore how agenda navigation may be accomplished underway in consultations covering multiple topics, we identified and analyzed one GP's communicative strategies. Design, setting, and subjects A qualitative observational case study with linguistic microanalysis of an exemplary consultation between a female patient with diabetes and her male GP. We used speech act theory to identify communicative actions that indicated agenda navigation by the GP in transitions between episodes concerning ten topics. Results Microanalysis revealed different aspects of agenda navigation by the GP using speech acts, especially ways of opening or closing an episode. The opening of episodes was characterized by speech acts accepting the patient's request to discuss a topic, mostly at the beginning of the consultation. Speech acts to inform or to request information from the patient dominated later in the consultation. The GP closed all episodes using speech acts to instruct or appraise the patient, or to make agreements and plans. Conclusion and practice implications Skilful agenda navigation is an important tool for consultations covering multiple issues and could be further developed for medical education. The opening and closing of episodes were vital communicative strategies supporting patient-centered communication in a complex consultation while maintaining the focus of the consultation agenda.KEY POINTS While traditional consultation models cover one health problem, GP consultations often include many patient issues in each session. Linguistic microanalysis of speech acts helped to identify communication strategies in a GP consultation with multiple topics. The GP conducted agenda navigation by distinctly opening and closing episodes concerning specific topics. Episodes were opened by accepting, informing, and requesting and closed by instruction, appraisal, making agreements, or plans.